TAX CHALLENGES OF DIGITAL ECONOMY IN INDONESIA - Susanna Hartanto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
E-commerce transactions emerged as a consequences of the new virtual business model that is used by some multinational entities expanding their business operations abroad in the international landscape. This study aims to explore ecommerce taxation in Indonesia including some factors like understandings and tax payer’s opinion of e-commerce taxation and current rule and tax mechanism of ecommerce which are supporting the implementation of e-commerce taxation. Factors studied related to taxation of e-commerce, including mechanism, monitoring system, and e-commerce transaction. Interviews were conducted from the side of fiscus (Directorate General of Taxation) and taxpayers in e-commerce industry. Data collection was used semi-structured interview, observation, and documentation. Data analysis of this research was descriptive method. The result of this study proves that taxation in e-commerce industry has not been implemented in a good manner. Socialization to e-commerce taxpayers should be conducted in more structured and comprehensive ways. Difficulties in the detection of e-commerce transactions bring its own problems, this is the biggest challenges in e-commerce transactions, namely the difficulty of the government to establish a clear and fair e-commerce tax rules. Recent government rule in November 2019 which accommodate economic substance from Unified Approach of OECD gives refreshment to those difficulties.